2021
DOI: 10.31557/apjcp.2021.22.8.2399
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sitting Time, and Quality of Life among Breast and Gynaecology Cancer Survivors

Abstract: Background: Increasing physical activity and reducing sitting time was recommended to cancer survivors after cancer treatment for sustained health and to enhance the quality of life. This study aimed to determine the association of physical activity and sitting time with quality of life among the Malay breast and gynaecological cancer survivors. Methods: A cross-sectional study was conducted among 95 breast and gynaecology cancer survivor subjects. The Malay International Physical Activity Questionnaire (IPAQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Nearly 70% of women in our study were overweight or obese, with a BMI ≥25 kg/m 2 . This is in line with findings from previous studies [26][27][28] and is expected in a population of endometrial carcinoma survivors as obesity or overweight is one of the main risk factors for this disease [1]. The cutoff of BMI ≥30 kg/m 2 may be more relevant for endometrial carcinoma survivors than BMI ≥25 kg/m 2 .…”
Section: Meeting Who Lifestyle Recommendationssupporting
confidence: 90%
See 2 more Smart Citations
“…Nearly 70% of women in our study were overweight or obese, with a BMI ≥25 kg/m 2 . This is in line with findings from previous studies [26][27][28] and is expected in a population of endometrial carcinoma survivors as obesity or overweight is one of the main risk factors for this disease [1]. The cutoff of BMI ≥30 kg/m 2 may be more relevant for endometrial carcinoma survivors than BMI ≥25 kg/m 2 .…”
Section: Meeting Who Lifestyle Recommendationssupporting
confidence: 90%
“…The study by Schleisinger and collegues [25], investigated several lifestyle factors and found the strongest association between BMI and global health status. Zainordin and colleagues, could however not demonstrate this association in a recent study among breast and gynecological cancer survivors [26]. This study assessed intensity of physical activity and sitting time by the international physical activity questionnaire (IPAQ).…”
Section: Global Health Statusmentioning
confidence: 85%
See 1 more Smart Citation
“…The associations between physical activity and muscular strength and HRQoL has also been reported in other ethnic populations [ 10 , 18 , 20 ]. In a cross-sectional study of 191 Chinese pediatric cancer survivors (aged 9 to 16 years), for instance, Cheung et al [ 34 ] demonstrated that higher PA was associated with better physical, emotional, social, and school functioning, and that greater handgrip strength was associated with better physical and emotional functioning.…”
Section: Discussionsupporting
confidence: 60%
“…Physical activity is also associated with reduced odds of developing sarcopenia and increased odds of reversing sarcopenia in cancer patients [ 10 ]. Substantial evidence from randomized trials supports the potential for physical activity to reduce cancer-related symptoms and improve physical functioning [ 14 , 15 , 16 ] and HRQoL [ 17 , 18 ]. Considering the therapeutic potential of physical activity and muscular strength against the symptoms of cancer and the side effects of anticancer treatments, physical activity is recommended highly before, during, and after treatment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%